CCL3 Promotes Cutaneous Wound Healing Through Recruiting Macrophages in Mice - Shi, Wanwan; Li, Xunsheng; Wang, Zhen; Li, Chenguang; Wang, Datao; Li, Chunyi (Cell transplantation, 2024)
Wound healing is a complex process, which involves three stages: inflammation, proliferation, and remodeling. Inflammation is the first step; thus, immune factors play an important regulatory role in wound healing. In this study, we focused on a chemokine, C-C motif chemokine ligand 3 (CCL3), which is often upregulated for expression during wound healing. We compared cutaneous wound healing at the histological, morphological, and molecular levels in the presence and absence of CCL3. The results showed that the wound healing rate in the wild-type and CCL3-/- + CCL3 mice was faster than that of CCL3-/- mice (P < 0.01), and application of CCL3 to wounds increased the healing rate. In the process of wound healing, the degree of reepithelialization and the rate of collagen deposition in the wound of CCL3-/- mice were significantly lower than those of wild-type mice (P < 0.01). The number of macrophages and the expression levels of tumor necrosis factor(TNF)-α and transforming growth factor (TGF)-β1 in the wounds of wild-type mice were much higher than those of the CCL3-/- mice. Removal of macrophages and CCL3-/- mice share similar phenotypes. Therefore, we infer that the wound healing requires the participation of macrophages, and CCL3 may play an important regulatory role through recruiting macrophages to the wound sites.